Successful stabilization and recovery in Mauritius - Gulhati, Ravi (World Bank WashingtonUS, 1990)
Presents a brief sketch of elements contributing to the economic and financial difficulties that accumulated in the late 1970s. Examines the political aspects as well as economic policy responses of three coalition governments in the 1980s. Offers lessons of experience, culled from the reform process aimed at stabilization and recovery.